Revitalisasi Bantaran Sungai sebagai Destinasi Pariwisata Low Budget berbasis Waterfront City di Sungai Deli Medan - Kharisma Roh Turang Gajah Manik; Ahmad Zulfikar; Isak Kelfin Pasaribu; Adalan Nur Daulay; Paskia Damanik; Khairun Nadia; Maulana Al Fathir (Arsir: Jurnal Arsitektur, 2026)
The Deli River area in Medan City has strong potential for further development as a low-budget waterfront-based tourist destination. With its historical and cultural value and strategic location, revitalization of this area could bring economic, social, and environmental benefits to local residents. This research aims to identify existing conditions and development potential, and design a revitalization strategy that supports sustainability. Using a descriptive qualitative approach, this study utilizes data from observations, interviews, and a literature review of relevant waterfront city design. Design elements such as accessibility, sustainability, and public space functionality are the primary focus for creating an inclusive, budget-friendly area. The expected end result is a design for the area with amenities such as green areas, pedestrian paths, an amphitheater, gazebos, restrooms, and communal areas along the riverbank, as well as supporting facilities such as park benches, lighting, and trash receptacles designed using local resources. The revitalization of the Deli River is expected to enhance its tourist appeal, maintain the region's cultural characteristics, and create a public space that benefits all residents of Medan City.